Chronic stress as a trigger for telogen effluvium: a psychophysiological aspect in the practice of a trichologist - Stupak, Iryna (Global Prosperity, 2026)
Abstract. Nowadays, the concept of “stress” is an integral part of our lives. We use it to describe our state of being out of our comfort zone too often, without thinking about the actual content of this term, the scale of morpho-functional, psycho-somatic manifestations and consequences. It is impossible to consider the effects of stress locally, because the mechanisms of its occurrence are not isolated processes, but parts of long functional chains that operate according to the “domino” principle, when one component, falling, pushes another onto the next and starts a chain reaction of falling. In the human body, which is a dynamic system and is represented by a complex of other dynamic systems, a similar principle of mutual activation operates, which can also return in a circle to the initiator and restart pathogenesis with new force. Using the example of stress-induced telogen effluvium, some components of the psychosomatic component in the development of alopecia are considered, the main axes and circles of interaction of the mechanism of hair loss due to the prolongation of the telogen phase of the hair follicle under stress, which occurs indirectly through the action of a number of hormones, such as, for example, the relationship between elevated cortisol levels and impaired microcirculation in the scalp; the direct effect of the nervous system on the hair follicle, impaired expression of biological substances (neurotransmitters) necessary for maintaining the microenvironment and the hair’s own homeostasis, and many others. Attention is focused on the ways of correction, not only surgical and medicinal, but also non-medicinal by using methods of stabilizing the human condition (gentle care rituals, relaxation techniques, work with trichological ampoules, massage), which can be provided to the patient as a client of the salon practice.